2018
DOI: 10.1093/trstmh/try020
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of hospital-acquired infections among adults in a tertiary hospital in north-western Nigeria

Abstract: The burden of HAIs is high and similar to other parts of Nigeria. There is a need for continued surveillance of HAIs in all the wards of the hospital in order to fully describe the extent of the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
1
11
2
2
Order By: Relevance
“…Neonatal and pediatric surgical specialties had the highest prevalence and represented more than 50% of all the HAI. The prevalence of HAI in the present study was higher than the 2.6-6.3% reported in previous retrospective studies conducted in Nigeria [6,13,14]. However, the current study is comparable to the cumulative prevalence of HAI in developing countries [7] and Ethiopia [19], but higher than the prevalence in Ghana [20], South Africa [21], Iran [22], the United States [2] and the European hospitals [4].…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Neonatal and pediatric surgical specialties had the highest prevalence and represented more than 50% of all the HAI. The prevalence of HAI in the present study was higher than the 2.6-6.3% reported in previous retrospective studies conducted in Nigeria [6,13,14]. However, the current study is comparable to the cumulative prevalence of HAI in developing countries [7] and Ethiopia [19], but higher than the prevalence in Ghana [20], South Africa [21], Iran [22], the United States [2] and the European hospitals [4].…”
Section: Discussioncontrasting
confidence: 71%
“…Bloodstream infections, particularly neonatal sepsis, surgical site infections and pneumonia were the most common HAIs in the current study, consistent with the findings of an Iranian study [22], but inconsistent with the results in other countries [2,4]. Previous studies conducted in Nigeria demonstrated that urinary tract infection (UTI) was the most common HAI [6,13].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In a Nigerian hospital, it was reported that among patients that developed hospital-acquired infections, 80%, 84% and 95% of S. aureus, E. coli, and P. aeruginosa isolates respectively were Multi-Drug Resistant (MDR). 27 In another study on agents of bacterial blood stream infections in Nigeria, a high prevalence of AMR against ampicillin, trimethoprim-sulfamethoxazole, tetracycline and cloxacillin was described. 28…”
Section: Perception Of Amrmentioning
confidence: 99%